Retificador trifásico semicontrolado para sistemas eólicos de carregamento de baterias - Santos, Francisco das Chagas Batista (2011)
The main objective of this work is to build a low cost CA/CC battery charging with high power factor to small energy wind power supply. The proposed topology has been chosen after a review of rectifiers’ characteristics used for this proposal. Unlike the others proposals, the topology was designed take in a count aspects that make it appropriated to operate in remote areas. A semi controlled three phase rectifier operating in high frequency was built with a reduced numbers of semiconductors. The system is powered by a synchronic generator turbine of permanent magnets A control unit runs in open loop with a control strategy of key switching operating in discontinuous conduction mode (DCM) that ensure high power factor and low harmonic distortion total, improving the power transfer efficiency. The prototype output power was 250 W, it was specified to charge a 48 V battery bank. Tests were conducted in low speed and wind power by 1 kW. A motor was drived as variable voltage charge to emulating wind conditions. Goods results were obtained like a power factor of 0.98 and the input current THD 18%, experimental results was carried out to validate the functionality of the proposed converter.